Extra Virgin Olive Oil and Nigella sativa Oil Produced in Central Italy: A Comparison of the Nutrigenomic Effects of Two Mediterranean Oils in a Low-Grade Inflammation Model - Laura Bordoni; Donatella Fedeli; Dennis Fiorini; Rosita Gabbianelli (MDPI AG, 2019)
Extra virgin olive (EVO) oil and Nigella sativa (NG) oil are two well-known Mediterranean foods whose consumption has been associated with beneficial effects on human health. This study investigates the nutrigenomic properties of two high quality EVO and NG oils in an in vitro model of low-grade inflammation of human macrophages (THP-1 cells). The aim was to assess whether these healthy foods could modulate inflammation through antioxidant and epigenetic mechanisms. When THP-1 cells were co-exposed to both lipopolysaccharides (LPS)-induced inflammation and oils, both EVO and NG oils displayed anti-inflammatory activity. Both oils were able to restore normal expression levels of DNMT3A and HDAC1 (but not DNMT3B), which were altered under inflammatory conditions. Moreover, EVO oil was able to prevent the increase in TET2 expression and reduce global DNA methylation that were measured in inflamed cells. Due to its antioxidant properties, EVO oil was particularly efficient in restoring normal levels of membrane fluidity, which, on the contrary, were reduced in the presence of inflammation. In conclusion, these data support the hypothesis that these Mediterranean oils could play a major role in the modulation of low-grade inflammation and metabolic syndrome prevention. However, NS oil seems to be more efficient in the control of proinflammatory cytokines, whereas EVO oil better helps to counteract redox imbalance. Further studies that elucidate the nutrigenomic properties of local produce might help to promote regional the production and consumption of high-quality food, which could also help the population to maintain and promote health.